Isolation of highly efficient potassium solubilizing bacteria and their effects on nutrient acquisition and growth promotion in tobacco seedlings - Jia-ning Gao; Meng-tao Xu; Ernest Uwiringiyimana (BMC Plant Biology)
Abstract Background Tobacco plants are typically high potassium (K)-demanding during growth and development, but the bioavailability of the nutrient in tobacco-growing soils is often limited. Aim and methodology The present study aimed at screening highly efficient potassium-solubilizing bacteria (KSB) through in vitro experiments, and to grasp their potential role in mineral dissolution for nutrients release. The effects of these bacterial inoculants on soil nutrient bioavailability, macronutrient acquisition, soil bacterial community characteristics, and tobacco seedling biomass were investigated through a greenhouse pot experiment. Results The in vitro experiments showed that the SKL51 (Paenibacillus sp.), SKT41 (Klebsiella oxytoca), and PTG11 (Enterobacter hormaechei) strains were more efficient at solubilizing K than the reference strain RT (Bacillus mucilaginosus). During the 7-day incubation with K-feldspar, the average solubilized potassium by SKL51, SKT41 and PTG11 was 28.8 ± 6.8, 30.1 ± 6.7 and 29.1 ± 1.0 μg mL−1, respectively. The highest potential K solubility enhanced by the three KSB was 55.1%, 39.0% and 41.1%, respectively. Additionally, these bacteria exhibited differences in their potential to solubilize other nutrients, with SKT41 enhancing the dissolution of feldspar the most for Si4+ (13.2 ± 2.9 μg mL−1), PTG11 for Ca2+ (174.1 ± 29.4 μg mL−1) and SKL51 for Mg2+ (52.7 ± 3.0 μg mL−1). The three KSB secreted various low-molecular-weight organic acids (LMWOAs) that were variably correlated with solubilized mineral nutrients. The results of the greenhouse pot experiment showed that soil inoculation with PTG11 was the most effective at increasing seedling height by 45% and dry biomass by 83%. The relative abundances of Acinetobacter, Asaia, Bacillus, Bacteroides, Faecalibacterium, Pseudoclavibacter and Sphingomonas, which are associated with the development of both root systems and plant aboveground parts increased significantly (p < 0.05), thereby contributing to shifts in soil bacterial community structure and correlating with improved soil properties. Conclusion PTG11 and SKL51 had significant effects on soil bacterial community structure, and nutrient mobilization, thereby promoting plant growth in support of ecological benefits and environmental friendliness.